Total and regional body composition of NCAA Division I collegiate female softball athletes - Czeck, M. A.; Raymond-Pope, C. J.; Stanforth, P. R.; Carbuhn, A.; Bosch, T. A.; Bach, C. W.; Oliver, J. M.; Dengel, D. R. (International Journal of Sports Medicine, 2019)
The purpose of this study was to evaluate total, regional, and throwing versus non-throwing arm body composition measures across the 4 major positions of NCAA Division I female softball players using dual X-ray absorptiometry (DXA) (n=128). Total and regional total mass (TM), fat mass (FM), lean mass (LM), bone mineral density (BMD), bone mineral content (BMC), and visceral adipose tissue were measured. Athletes were separated into: pitchers (n=32), catchers (n=13), outfielders (n=39), and infielders (n=44). ANOVA and Tukey`s HSD assessed total and regional differences between positions. Although no significant total or regional LM differences were observed across positions, outfielders had significantly (p=0.006-0.047) lower total-body, arm, and trunk TM and FM, leg FM, and leg BMC in comparison to pitchers. The throwing arm had significantly (p<0.0001-0.018) greater LM, BMD, and BMC than the non-throwing arm for all positions. Notably, there were minimal body composition differences among softball positions, with the primary differences being that pitchers had larger total and regional fat values than outfielders. The throwing arm of all positions had greater LM, BMD, and BMC than the non-throwing arm. These values can be used by coaches and trainers as descriptive DXA data for collegiate softball players.